"O núcleo supraquiasmático e o folheto intergeniculado do mocó (Kerodon rupestris): Projeções retinianas e caracterização imuno-histoquímica - Nascimento Júnior, Expedito Silva do (2007)
In this study, two circadian related centres, the suprachiasmatic nucleus (SCN) and the intergeniculate leaflet (IGL) were evaluated in respect to their cytoarchitecture, retinal afferents and chemical content of major cells and axon terminals with a tract tracer and immunohistochemical techniques in the rock cavy (Kerodon rupestris), a Brazilian caviidae rodent species. The rock cavy SCN is innervated in its ventral portion by terminals from the predominantly contralateral retina. It also contains neurophisin and vasoactive intestinal polypeptide immunoreactive cell bodies and neuropeptide Y and enkephalin immunopositive fibres and terminals and is marked by intense GFAP immunoreactivity. The IGL receives a predominantly contralateral retinal projection, contains neuropeptide Y and nitric oxide synthase producing neurons and enkephalin immunopositive terminals and is characterized by dense GFAP immunoreactivity. This is the first report examining the neural circadian system in a crepuscular rodent species for which circadian properties have been described. The results are discussed comparing with what has been described for other species and in the context of the functional significance of these centres